Influence of Qigong training on reduction of harmful computer habits and their danger for students with weak health - M.D. Kudryavtsev; I.E. Kramida (Physical Education of Students, 2017)
Purpose: to show influence of health related Qigong training of reduction of harmful computer habit and their danger for students with weak health. Material: 1st-3rd year students of Krasnoyarsk were the object of the research (n=1158). Students were trained by discipline “Physical culture” for main health group (no health problems). Students with weak health were trained by Qigong program (n=129). Results: Qigong training reduces total time of students, which they spent for computer habits. The most frequent of all students is internet. The spread of this habit in students of all tested groups does not change noticeably in the course of study. Qigong training reduces the quantity of students, who spend dangerously much time every of three computer habits. Conclusions: Qigong training of reduction of harmful computer habit and their danger for students with weak health. It is more effective in reduction of time, spent for all harmful habits than typical physical culture trainings.